COORS, M. (ed.) (2022). Moralische Dimensionen der Verletzlichkeit des Menschen. Berlín-Brandenburgo: De Gruyter. - Argüelles Rozada, Isabel (Daimon Revista Internacional de Filosofia, 2024)
Reseña de COORS, M. (ed.) (2022). Moralische Dimensionen der Verletzlichkeit des Menschen. Berlín-Brandenburgo: De Gruyter.